Distribution patterns and functional traits of nematode meiofauna assemblages in Sado Estuary (Portugal) - Rosmaninho, Teresa Charrua (2020)
Estuaries are naturally stressed systems with a high degree of variability in their physical-chemical characteristics. The natural gradient of salinity, linked with other gradients (e.g. sediment type and dynamics, oxygen availability, temperature and current speed) are well documented as important factors in determining temporal and spatial variations in meiofauna communities. Among the estuarine biological components, meiobenthic communities are good indicators of environmental conditions and therefore changes in their density, diversity, structure and functioning indicate important alterations of the ecosystem. In fact, the phylum Nematoda are the ideal indicator group because they are the most diverse and abundant meiofaunal metazoans of aquatic habitats. The main aim of this study was to advance the general understanding of the spatial distribution patterns of the nematode assemblages along the Sado estuarine gradient. There were analysed structural components of nematode assemblages (abundance, species richness and diversity metrics) as well as functional attributes such as Maturity Index and Trophic Diversity Index. Additionally, multivariate analysis on community data was performed, together with Redundancy Analysis to understand which environmental factors explain the variations in the community. The results showed significant differences in the nematode structural assemblage patterns among the estuary sections. The abundance and diversity of nematodes were related with environmental variables including TOM (Total Organic Matter) concentration, the sediment grain size and the levels of dissolved oxygen. The sections with the highest TOM and lowest oxygen concentration were dominated by the opportunistic genera that were more resistant to unfavourable conditions and were responsible for low species richness. Functional attributes did not exhibit any significant differences among Estuary sections. As a conclusion, nematodes assemblages turned to be good bioindicators of heterogenous environmental conditions of this estuary, especially regarding the detection of sites with higher TOM concentration; Padrões de distribuição espacial das comunidades de nematodes bentónicos e das suas características funcionais no Estuário do Sado (Portugal). Resumo: Os estuários são sistemas naturalmente perturbados, com grande variabilidade nas suas características físicas e químicas. O gradiente natural de salinidade, associado a outros gradientes (por exemplo, granulometria, hidrodinamismo, oxigénio, temperatura e correntes das marés), estão bem documentados como sendo fatores determinantes para as variações temporais e espaciais das comunidades de meiofauna. Entre os diferentes componentes biológicos associados a um ambiente estuarino, as comunidades meiobentónicas são consideradas bons indicadores das condições ambientais. Isto porque, quando existem alterações na sua abundância, estrutura funcional pode ser resultado do efeito de alterações nos ecossistemas. Nematoda é o grupo taxonómico da meiofauna que em geral é mais abundante e é considerado um bom indicador ecológico. O principal objetivo deste estudo é analisar o padrão de distribuição espacial das comunidades de nematodes ao longo do gradiente estuarino do estuário do Sado. Foram analisadas variáveis ambientais consideradas determinantes para os padrões de distribuição da abundância e composição de géneros ao longo do estuário do Sado, assim como para a distribuição dos atributos funcionais das comunidades. Através da análise multivariável das abundância e diversidade comunidades foi possível determinar os fatores ambientais que melhor explicam as variações na comunidade. Também foi feita analise multivariada com base nos dados das comunidades tais como a Analise de Redundância para entender quais os fatores ambientais que melhor explicam as variações das comunidades. Os resultados mostram diferenças significativas na densidade e diversidade das comunidades de nematodes entre as várias secções do estuário. A densidade de nematodes apresentou relação com diferentes variáveis ambientais analisadas, tais como a concentração de TOM (matéria orgânica total), granulometrias e consequentemente os níveis de oxigénio dissolvido. Nas seções com maior TOM e menor concentração de oxigênio verificou-se que os géneros oportunistas eram mais abundantes, sendo estes mais resistentes a condições desfavoráveis e responsáveis pela baixa riqueza de espécies. As características funcionais não apresentaram diferenças significativas entre as seções do estuário. Pode concluir-se que as comunidades de nematodes se tornaram bons bioindicadores de condições ambientais heterogêneas deste estuário, principalmente quanto à deteção de sítios com maior concentração de TOM.